How Should Commodities be Taxed? A Counterargument to the Recommendation in the Mirrlees Review - Spencer Bastani; Sören Blomquist; Jukka Pirttilä (Center for Economic Studies and ifo Institute (CESifo), 2013)
The Mirrlees Review recommends that commodity taxation should in general be uniform, but with some goods consumed in conjunction with labour supply (such as child care) left untaxed. This paper examines the validity of this claim in an optimal income tax framework. Contrary to the recommendation of the Review, our theoretical results imply that even if all goods other than the good needed for working are separable from leisure, the optimal tax on these goods should not be uniform. Instead, goods with larger expenditure elasticities should be discouraged relatively more by the tax system. If the government fully subsidises the cost of the good needed for working, then commodity taxation is uniform under the standard separability assumption. Our results imply that the optimal commodity tax system is dependent on the expenditure side of the government. A calibration exercise presented in the paper suggests that these results can be quantitatively important.
Keywords: H21; H42; 330; income taxation; commodity taxation; public provision; separability